Effects of number of substituents and molecular weight of polyamines on the non-cyanide alkaline zinc plating process - Nam, Truong Thi; Thang, Le Ba; Bao, Le Duc; Khuong, Nguyen Van (Vietnam Journal of Science and Technology, 2021)
The effects of the number of substituents and molecular weight of polyamines in the non-cyanide alkaline plating bath on the morphology, brightness and bright ranges of zinc electrodeposited coating and cathodic polarization, cyclic voltammogram on the non-cyanide alkaline zinc plating process were investigated. Cathodic polarization measurements showed that the polyamines all increased cathodic polarization of the plating process and shifted the zinc reduced potential to a more negative direction. However, cycle voltammogram curves of the 5 continuous cycles shows that the quaternary polyamine Q7-20 has a more stable adsorption and desorption processes than the secondary polyamine Bt18 has.